ANALYSIS OF THE TRANSLATION OF INDONESIAN LYRICS INTO ENGLISH IN ANNETH DELLIECIA’S SONG “MUNGKIN HARI INI HARI ESOK ATAU NANTI” - Yuwanti, Riska Rahma; Afifulloh, M; Widyasari (Loquēla (Journal of Linguistics, Literature, and Education), 2024)
The purpose of this study is to explore the translation process by Emma Heesters in rending Anneth Delliecia’s song lyrics “Mungkin hari ini hari esok atau nanti”. The translation method in question places a strong emphasis on the source or target languages. Additionally, the author sought to ascertain the rationale behind the utilization of this specific translation methodology. This research method used descriptive analysis with a qualitative approach in other words this is to describe the data that has been obtained and also a case as a design. The lyrics of the song entitled mungkin hari ini esok atau nanti by Emma Heesters, are the subject of this analysis. The author gathers data through the process of documentation. This involves collecting the lyrics of the Indonesian and English versions of the song and listening to the song. The translation method employed in this instance is based on the V diagram theory, which was first proposed by Newmark. The results indicated that the predominant translation method employed was one that placed significant emphasis on the target language, with some portions of the lyrics also emphasizing the source language. It can be posited that Emma Heesters’ tendency to utilize a translation method that prioritised the target language was driven by the necessity to align the translation with the desired intonation or tone of the song.